Odnos nupcijaliteta i nataliteta na području Zenice u periodu 1929–1941. i danas / The Nuptiality and Birth Rate Correlation in the Zenica Dostrict from 1929 to 1941 and Today - Huseinspahić, Ajdin (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Starting from the hypothesis that the number of marriages had a direct impact on the total number of births in the Zenica county from 1929 to 1941, and questioning the proportionality of the variables in the City of Zenica from today's time perspective, the focus of the work have found themselves social tendencies in marital relations in Zenica in that period compared to their present understanding. For the purpose of proving or disproving hypotheses data were collected from the registers of births, marriages and deaths, after which was performed to compare them and necessarily bringing in correlation with the current social tendencies when it comes to marriage and its role in increasing the birth rate in the area of Zenica.